BRCA1 mutations drive oxidative stress and glycolysis in the tumor microenvironment: Implications for breast cancer prevention with antioxidant therapies - Martinez-Outschoorn, Ubaldo E. (Landes Bioscience, 2012)
Mutations in the BRCA1 tumor suppressor gene are commonly found in hereditary breast cancer. Similarly, downregulation of BRCA1 protein expression is observed in the majority of basal-like breast cancers. Here, we set out to study the effects of BRCA1 mutations on oxidative stress in the tumor microenvironment. To mimic the breast tumor microenvironment, we utilized an in vitro co-culture model of human BRCA1-mutated HCC1937 breast cancer cells and hTERT-immortalized human fibroblasts. Notably, HCC1937 cells induce the generation of hydrogen peroxide in the fibroblast compartment during co-culture, which can be inhibited by genetic complementation with the wild-type BRCA1 gene. Importantly, treatment with powerful antioxidants, such as NAC and Tempol, induces apoptosis in HCC1937 cells, suggesting that microenvironmental oxidative stress supports cancer cell survival. In addition, Tempol treatment increases the apoptotic rates of MDA-MB-231 cells, which have wild-type BRCA1, but share a basal-like breast cancer phenotype with HCC1937 cells. MCT4 is the main exporter of L-lactate out of cells and is a marker for oxidative stress and glycolytic metabolism. Co-culture with HCC1937 cells dramatically induces MCT4 protein expression in fibroblasts, and this can be prevented by either BRCA1 overexpression or by pharmacological treatment with NAC. We next evaluated caveolin-1 (Cav-1) expression in stromal fibroblasts. Loss of Cav-1 is a marker of the cancer-associated fibroblast (CAF) phenotype, which is linked to high stromal glycolysis, and is associated with a poor prognosis in numerous types of human cancers, including breast cancers. Remarkably, HCC1937 cells induce a loss of Cav-1 in adjacent stromal cells during co-culture. Conversely, Cav-1 expression in fibroblasts can be rescued by administration of NAC or by overexpression of BRCA1 in HCC1937 cells. Notably, BRCA1-deficient human breast cancer samples (9 out of 10) also showed a glycolytic stromal phenotype, with intense mitochondrial staining specifically in BRCA1-deficient breast cancer cells. In summary, loss of BRCA1 function leads to hydrogen peroxide generation in both epithelial breast cancer cells and neighboring stromal fibroblasts, and promotes the onset of a reactive glycolytic stroma, with increased MCT4 and decreased Cav-1 expression. Importantly, these metabolic changes can be reversed by antioxidants, which potently induce cancer cell death. Thus, antioxidant therapy appears to be synthetically lethal with a BRCA1-deficiency in breast cancer cells and should be considered for future cancer prevention trials. In this regard, immunostaining with Cav-1 and MCT4 could be used as cost-effective biomarkers to monitor the response to antioxidant therapy.